2005
DOI: 10.1097/01.mlg.0000163755.21035.8f
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant EGFR and Chromosome 7 Associate with Outcome in Laryngeal Cancer

Abstract: Measurements of EGFR and chromosome 7 FISH status, and to a lesser extent EGFR expression, have potential value in treatment planning for patients with laryngeal SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 13 publications
1
19
1
2
Order By: Relevance
“…Although, the rate limiting polysomy number of biological significance is not known, our analysis of categorical groupings showed that even low levels of chromosomal duplication affected rate of progression to death (Table 2, Figure 3). Similar to other carcinomas, polysomy/EGFR copy number in our study correlated with poor prognosis suggesting DNA aneuploidy and/or relative increase in EGFR copy number plays an adverse biological role (14, 24, 26-28). Interestingly, previous reports have shown that response to cetuximab and panitumumab, two epidermal growth factor inhibitors (tyrosine kinase inhibitors) correlated with EGFR copy number (polysomy and amplification) in colonic adenocarcinoma (25) and not mutational status.…”
Section: Discussionsupporting
confidence: 83%
“…Although, the rate limiting polysomy number of biological significance is not known, our analysis of categorical groupings showed that even low levels of chromosomal duplication affected rate of progression to death (Table 2, Figure 3). Similar to other carcinomas, polysomy/EGFR copy number in our study correlated with poor prognosis suggesting DNA aneuploidy and/or relative increase in EGFR copy number plays an adverse biological role (14, 24, 26-28). Interestingly, previous reports have shown that response to cetuximab and panitumumab, two epidermal growth factor inhibitors (tyrosine kinase inhibitors) correlated with EGFR copy number (polysomy and amplification) in colonic adenocarcinoma (25) and not mutational status.…”
Section: Discussionsupporting
confidence: 83%
“…The involvement of EGFR signaling has been demonstrated in various cellular processes ranging from normal growth and differentiation to oncogenesis (40)(41)(42). Aberrant EGFR as a result of receptor mutation and/or overexpression occurs in NSCLC (43) laryngeal cancer (44), pancreatic cancer (45). Our previous study indicated that EGFR activation promotes HNSCC cell migration and invasion by inducing an EMT-like phenotypic change and MMP-9-mediated degradation of E-cadherin into soluble E-cadherin (sE-cad) associated with activation of ERK-1/2 and PI3K signaling pathways (25).…”
Section: Discussionmentioning
confidence: 99%
“…¼ not available. 7 This dysplastic lesion contained one part with small nuclei, punctated HPV and chromosome disomy and another part with large nuclei, granular HPV and polysomic chromosome numbers.…”
Section: Hpv16-positivity and Chromosome Stability Are Associated Witmentioning
confidence: 99%
“…[4][5][6] We and others have shown that alterations in chromosome 1 and 7 copy numbers detected by FISH are frequently found in head and neck (pre)malignancies. 7,8 On the basis of imbalances in chromosome 1 and 7 copy number ratios, we were able to reliably predict malignant progression and tumor recurrence. [8][9][10] In these cases, the chromosome 1 copy number most often equalled the average copy number of all chromosomes (ploidy) in the lesions, whereas generally higher copy numbers for chromosome 7 were detected.…”
mentioning
confidence: 99%